The Best Advertisement a City Can Have: Public Health Services in Vancouver, 1886-1888 - Andrews, Margaret (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1984)
Vancouver was unlike many nineteenth centry Canadian cities in that it readily undertook to provide reasonably extensive public health services — a city hospital, waste disposal and drainage, a modern water supply, and health inspection. Provision of those services got fairly under way in the city's first two years, at which time (as later), those interested in the city's growth, who directed public expenditure there as in most cities of the time, encouraged up-to-date public health services as signs of municipal progress likely to attract additional settlers and capital. Public expenditures relating to health were supported as attractants which augmented the city's natural climatic advantages.